Cardiac infarction caused by PD-1 inhibitor during small cell neuroendocrine carcinoma of the ureter treatment: A case report - Li, Xiaoying; Wen, Jing; Li, Hongtao; Huang, Yan; Zhou, Hongliang (Frontiers in Oncology, 2023)
Although small cell neuroendocrine carcinoma of the ureter (ureteral SCNEC) is rare, it always leads to a poor prognosis. Also, no treatment recommendation has been given for ureteral SCNEC, with only PD-1/PD-L1 inhibitors being used for its treatment. We present a case of atypical symptoms of cardiac infarction caused by a PD-1 inhibitor used in the treatment of ureteral SCNEC. We hope to alleviate concerns about the potential cardiac toxicity of PD-1/PD-L1 inhibitors in ureteral SCNEC patients.